Informal landfill contributes to the pollution of microplastics in the surrounding environment - Wan, Yong; Chen, Xin; Liu, Qian; Hu, Hongjuan; Wu, Chenxi; Xue, Qiang (Environmental pollution (1987), 2022)
A large amount of plastic waste is generated yearly worldwide, and landfills are commonly used for the disposal of plastic waste. However, burying in landfill does not get rid of the plastic waste but leave the problem to the future. Previous works have showed that microplastics are presented in the landfill refuse and leachate, which might be potential sources of microplastics. In this work, characteristics of microplastic pollution in an informal landfill in South China were studied. Landfill refuse, underlying soil, leachate, and groundwater samples were collected from different sites within and around the landfill. Results show that microplastics in the landfill refuse and underlying soil varied from 590 to 103,080 items/kg and from 570 to 14,200 items/kg, respectively. Most of the microplastics are fibrous, small sized, and transparent. Polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET) are major polymer types. Scanning electron microscope (SEM) images and Fourier Transform Infrared (FTIR) spectra of the microplastic samples indicate varying degree of weathering. Microplastic abundances in the landfill leachate and groundwater ranged from 3 to 25 items/L and from 11 to 17 items/L, respectively. Microplastics detected in the landfill leachate and groundwater are even smaller compared with those in the refuse and underlying soil and their polymer types are more diverse. This work demonstrated that microplastics presented in an informal landfill without sufficient protection can leak out to the surrounding environment. The microplastic pollution originated from informal landfills should receive more attentions. [Display omitted] •Characteristics of microplastic pollution were studied in an informal landfill.•Microplastics were detected in landfill refuse, leachate, underlying soil, and groundwater.•Microplastic characteristics suggest their formation are related to the weathering in landfill.•Informal landfills are important sources of microplastic pollution to the environment.